68Ga-FAPI and 18F-FDG PET/CT Images in a Patient With Extrapulmonary Tuberculosis Mimicking Malignant Tumor. (November 2020) - Gu, Bingxin; Luo, Zhiguo; He, Xinhong; Wang, Jian; Song, Shaoli
Abstract : Abstract: Extrapulmonary tuberculosis (TB) is difficult to diagnose. Here, we report a case of extrapulmonary TB in a 68-year-old woman presented with mental fatigue, poor appetite, and weight loss. 18 F-FDG PET/CT revealed elevated 18 F-FDG uptake in the left inferior cervical, left supraclavicular, mediastinal, and splenic hilum lymph nodes and spleen, which were suspected of malignant tumor. To further differentiate benign and malignant diseases, 68 Ga-FAPI PET/CT was performed. 68 Ga-FAPI PET/CT also showed intense 68 Ga-FAPI uptake in the previously mentioned FDG-avid lesions. However, biopsy of the left supraclavicular lymph node demonstrated the presence of TB.